2020
DOI: 10.3390/ijerph17010307
|View full text |Cite
|
Sign up to set email alerts
|

Does Daily Physical Activity Level Determine the Physical Efficiency of Children After Treatment of Leukemia?

Abstract: The aim of the study was to assess daily physical activity level and its influence on the physical efficiency of children after the treatment of leukemia. The study was comprised of 34 children (23 boys and 11 girls) after the treatment of acute lymphoblastic leukemia or myeloid leukemia (mean age of 11.29 ± 2.81 years, mean body height of 146.88 ± 16.11 cm, and mean body weight of 43.68 ± 13.93 kg). The mean time since treatment completion was 3.09 ± 1.80 years. The level of physical activity was assessed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The results showed that adolescents who participated in high-intensity PA performed better and had shorter test times. Malicka et al [13] also evaluated the level of PA in adolescents and its impact on physical tness, nding a positive correlation between high-intensity PA and running performance. Additionally, research has shown that regular participation in PA can improve and enhance adolescents' neural reaction speed [14] .…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that adolescents who participated in high-intensity PA performed better and had shorter test times. Malicka et al [13] also evaluated the level of PA in adolescents and its impact on physical tness, nding a positive correlation between high-intensity PA and running performance. Additionally, research has shown that regular participation in PA can improve and enhance adolescents' neural reaction speed [14] .…”
Section: Introductionmentioning
confidence: 99%